Stereospecific Ring Contraction of Bromocycloheptenes through Dyotropic Rearrangements via Nonclassical Carbocation–Anion Pairs - Goh, Shermin S; Champagne, Pier Alexandre; Guduguntla, Sureshbabu; Kikuchi, Takashi; Fujita, Makoto; Houk, K. N; Feringa, Ben L (Journal of the American Chemical Society, 2018)
Experimental and theoretical evidence is reported for a rare type I dyotropic rearrangement involving a [1,2]-alkene shift, leading to the regio- and stereospecific ring contraction of bromocycloheptenes. This reaction occurs under mild conditions, with or without a Lewis acid catalyst. DFT calculations show that the reaction proceeds through a nonclassical carbocation–anion pair, which is crucial for the low activation barrier and enantiospecificity. The chiral cyclopropylcarbinyl cation may be a transition state or an intermediate, depending on the reaction conditions.